Life and art : essays - Russo, Richard, 1949- (Alfred A. Knopf, 2025)
"Sharp, tender, extraordinarily intimate reflections on work, culture, love and family from the Pulitzer Prize winning author of SOMEBODY'S FOOL and THE DESTINY THIEF"--